2019
DOI: 10.1007/s12020-019-01852-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes and presence of autoantibodies against zinc transporter 8 and glutamic decarboxylase at diagnosis and at follow up of Graves’ disease

Abstract: Purpose The aim of this work was to investigate, in patients with newly diagnosed Graves’ disease (GD), the frequency of islet autoantibodies including autoantibodies against Zink transporter 8 (ZnT8A), as well as to investigate the relation between thyroid autoantibodies, islet autoantibodies and diabetes both before GD diagnosis and at follow-up. Methods Blood samples from 278 patients with newly diagnosed GD were analyzed for autoantibodies against glutamic acid deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…The strong ZnT8 staining could been observed in almost all of the thyroid follicular cells and some of the cytoplasm and the perinuclear area of the hyperplastic C cells. In accordance with the observations mentioned before, ZnT8 was identified to be a major autoantigen in human type 1 diabetes and localized into insulin secretory granules (15,23), and it also expressed in other secretory cell types of murine like pancreatic α islet cells, thyroid cubical cells and adrenal gland cortex cells (24), so our data further confirm the widespread role of ZnT8 in the endocrine system (15,24,25) . In addition, we observed significant differences in the level of ZnT8A between T1DM with AITD and AITD, while there were no statistical differences between AITD and nAITD or healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…The strong ZnT8 staining could been observed in almost all of the thyroid follicular cells and some of the cytoplasm and the perinuclear area of the hyperplastic C cells. In accordance with the observations mentioned before, ZnT8 was identified to be a major autoantigen in human type 1 diabetes and localized into insulin secretory granules (15,23), and it also expressed in other secretory cell types of murine like pancreatic α islet cells, thyroid cubical cells and adrenal gland cortex cells (24), so our data further confirm the widespread role of ZnT8 in the endocrine system (15,24,25) . In addition, we observed significant differences in the level of ZnT8A between T1DM with AITD and AITD, while there were no statistical differences between AITD and nAITD or healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…Out of 56 studies included in the systematic review, 25 were case‐control studies, 24‐47 17 were cohort studies 48‐64 and 14 were cross‐sectional studies 65‐78 . No clinical trials met the criteria used in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…ZnT8A is the recently identified new marker of autoimmunity in diabetes. Jonsdottir et al 22 recruited 278 patients with newly diagnosed GD for detecting GADA, IA-2A, three variants of ZnT8A, and they observed that 7.6% of them were positive for ZnT8A at diagnosis. Rydzewska's study, which was consisted of 44 children with GD, 65 children with HT, 199 children with T1DM with or without AITDs and 58 control children 23 , reported the overall prevalence of ZnT8A with AITD was 9.2%, with a similar prevalence of ZnT8A in both GD (9.1%) and HT (9.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have showed the prevalence rate of thyroid autoantibodies ranging from 3.7–35% in T1DM patients, some of which suggested the associations between thyroid autoantibodies and islet autoantibodies ( 10 , 11 , 12 , 13 , 14 ). However, little work has been done on the anti-islet autoimmune status in non-diabetic patients with AITD ( 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ). As summarized in Supplementary Table 1 (see section on supplementary materials given at the end of this article), the prevalence rates of glutamic acid decarboxylase autoantibodies (GADA), islet cell autoantibodies (ICA), insulinoma-associated antigen 2 autoantibodies (IA-2A) and insulin autoantibodies (IAA) in patients with AITD were either slightly or significantly higher than those in healthy controls (HC), indicating the distinct value of studying islet immune status in AITD.…”
Section: Introductionmentioning
confidence: 99%